Association between social support, functional status, and change in health‐related quality of life and changes in anxiety and depression in colorectal cancer patients. Issue 9 (19th December 2016) - Gonzalez‐Saenz de Tejada, M.; Bilbao, A.; Baré, M.; Briones, E.; Sarasqueta, C.; Quintana, J.M.; Escobar, A.
Abstract: Objective: The aim of this study was to explore the association between baseline social support, functional status, and change in health‐related quality of life (HRQoL) in colorectal cancer patients and change in anxiety and depression measured by Hospital Anxiety and Depression Scale (HADS) at 1 year after surgery. Methods: Consecutive patients who were due to undergo therapeutic surgery for the first time for colon or rectal cancer in 9 hospitals in Spain were eligible for the study. Patients completed the following questionnaires before surgery and 12 months afterward: 1 HRQoL instrument, the European Organization for Research and Treatment of Cancer Core Quality of Life Questionnaire; a social support questionnaire, the Duke‐UNC Functional Social Support Questionnaire; the Barthel Index, to assess functional status; the HADS, to assess anxiety and depression; and questions about sociodemographic information. General linear models were built to explore the association between social support, functional status, and change in HRQoL and changes in anxiety and depression 12 months after surgery. Results: A total of 947 colorectal cancer patients took part in the study. Patients' functional status, social support, and change in HRQoL were associated with changes in anxiety and depression. Greater social support and improvements in physical, cognitive, and social functioning and in insomnia resulted in improvements in anxiety and depression. No functionally independent patients were associated with lesser improvements in anxiety and depression. Conclusions: Colorectal cancer patients who have more social support, are functionally independent and have higher improvements in HRQoL may have better results in anxiety and depression at 1 year after surgery, adjusting for age, gender, location, occupation, and baseline HADS scores.